Analysis of the Usefulness of the Public Works and Spatial Planning Office Website Using the Webuse Method and Heuristic Evaluation - Rosada, Amrina; Saikin, Saikin; Tantoni, Ahmad (Internet of Things and Artificial Intelligence Journal, 2024)
In this modern era, the existence and usefulness of websites have become an undeniable necessity. The internet has set the stage for websites to become a vital tool in various aspects of life, not only as a means of disseminating information but also as a platform for improving efficiency and economic growth. However, various problems often occur to website users, the lack of notification or feedback after users act. And the lack of information updates. For example on the Website of the Public Works and Spatial Planning Office of West Lombok Regency web. This website still does not use two-way communication commonly called two-way communication, so some problems might arise such as a lack of ability to receive direct feedback from users, and website owners lose the opportunity to understand user needs. To overcome the above problems, the author conducted website usability research using the Heuristic Evaluation Method and the Webuse Method. To improve website usability regarding information services for users. And with the results of the PUPR Office website has shortcomings in providing information updates in the form of announcements and various other information. and the lack of an attractive appearance on the website menu. Therefore, researchers provide recommendations for improvement in providing information to users of the website of the Public Works and Spatial Planning Office of West Lombok Regency.